PENGARUH METODE KONSELING ASI PADA MASA NIFAS TERHADAP KEJADIAN PUTING SUSU LECET - Siti Noor Hasanah; Friscila, Ika (LPPM Universitas Sari Mulia, 2023)
Background:The impact on infants who do not receive breast milk (ASI) includes jaundice due to insufficient intake, non-ideal body weight, dental caries, and increased vulnerability to infections and diarrhea. Successful breastfeeding must be supported by effective breastfeeding practices. Healthcare facilities need trained breastfeeding counselors who are competent in helping mothers breastfeed exclusively for six months. Midwives, as counselors, must be able to guide pregnant women, especially first-time mothers, regarding breastfeeding. Objective:To determine the effect of breastfeeding counseling on the incidence of nipple soreness in postpartum mothers. Method:This is a quantitative study using a case-control design, with breastfeeding counseling as the independent variable and nipple soreness as the dependent variable. The sample consisted of postpartum mothers from 7 to 14 days postpartum, totaling 40 participants with a 1:1 ratio between the control and comparison groups. Data were analyzed using univariate (frequency distribution) and bivariate (Chi-square) analysis. Results:There were 20 respondents in the control group and 20 in the intervention group. Of the 40 respondents, 14 (35%) experienced nipple soreness. Conclusion:There is an effect of breastfeeding counseling methods on the incidence of nipple soreness in postpartum mothers. Keywords:Breastfeeding Counselor, Breastfeeding Counseling, Postpartum, Nipple Soreness